Palladium-Catalyzed Olefination of Aryl C–H Bonds by Using Directing Scaffolds - Bag, Sukdev; Maiti, Debabrata (Synthesis, 2016)
Site selective C–H bond activation/C–C bond formation is an ideal target for organic chemists owing to the ubiquitous nature of C–H bonds in natural products. A particular aryl C–H bond can be predictably activated by a directing group. However, the majority of strong and weak coordinating directing groups have been implemented for ortho-C–H bond activation/C-alkenylation. More recently, meta-C–H functionalization has been promoted by fine-tuning directing templates. In this short review, we have summarized recent progress in palladium-catalyzed directing group/template-assisted ortho/meta-C–H olefination.1 Introduction2 Proximal C–H Olefination3 Distal C–H Olefination4 Conclusions
Keywords: palladium; directing groups; olefination; ortho/meta-C–H bond; removable auxiliary